Perancangan Ekonomis dan Teknis Pembangkit Listrik Tenaga Surya di SD Bintang Juara Semarang - Ikhlash Rakhmanta; Gunawan Gunawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Indonesia's geographical position along the equator provides immense potential for renewable energy development, particularly solar power. Semarang, a city with high solar irradiance, is an ideal location for implementing solar energy solutions. SD Bintang Juara, situated at Jalan Dewi Sartika No. 17A, exhibits promising potential for an on-grid solar power plant (PLTS) due to its average solar radiation intensity of 5.4 kWh/m²/day. The school's energy demand of 67.045 kWh daily incurs a monthly electricity cost of Rp 2,600,000.00, which can be substantially reduced by offsetting 50% of the load with solar energy. This study employs a quantitative approach, analyzing solar radiation data, building orientation, and energy load to design a cost-effective and technically sound PLTS system. Findings reveal both technical and economic feasibility, with projected electricity production supporting a significant portion of the school’s needs. Over a 15-year operational period, the PLTS system is estimated to generate a total revenue of Rp 64,151,108.00. This initiative highlights the potential for renewable energy to reduce costs and promote sustainability in educational institutions, paving the way for broader applications across similar contexts.